Edukasi Pencegahan Penipuan Digital dan Perlindungan Data Pribadi bagi Siswa SMA Amanatul Ummah di Era Digital - Dina Anggraeni Susesti; Mohammad Ghofirin; Dwi Novitasari; Arinda Tri Apriliyah; Dhini Yuliana Siska (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to improve the understanding of students at SMA Amanatul Ummah Surabaya about methods to prevent digital fraud and protect personal data. The activity was carried out through interactive lectures, discussions, case simulations, and Q&A sessions involving 40 students. To evaluate the results, pre-tests and post-tests were conducted to measure the participants' understanding. The evaluation results showed that the average score of the participants increased from 68.25 to 91.05, or by 33.41%. This activity effectively enhances students' digital literacy and encourages safer and more responsible digital behavior.